The mitogenome of the jumping bristletail Trigoniophthalmus alternatus (Insecta, Microcoryphia) and the phylogeny of insect early-divergent lineages. Issue 2 (3rd July 2019) - Leo, Chiara; Nardi, Francesco; Frati, Francesco; Fanciulli, Pietro Paolo; Cucini, Claudio; Vitale, Matteo; Brunetti, Claudia; Carapelli, Antonio
Abstract: The complete mitochondrial genome of the machilid Trigoniophthalmus alternatus (Silvestri 1904) is herein described and applied to phylogenetic analyses, inclusive of the most early-divergent lineages of hexapods. Both gene content and order generally conform with the organization of the arthropods' mitochondrial genome. One gene translocation involving trnA is the autapomorphic character observed in this species. Another peculiar molecular feature is the long size of the A + T-rich region, due to the occurrence of repeat units. The phylogenetic analyses support the typical placement, along the hexapods' tree, of Ectognatha, Monocondylia and Dicondylia, with Diplura as the adelphotaxon of all true insects.